The effect of topical ethanol extract of Cotinus coggygria Scop. on cutaneous wound healing in rats - ŞEN, ALİ; OKUYAN, BETÜL; AKAKIN, DİLEK; AKSOY, HALİL; BİTİŞ, LEYLA; SANCAR, MESUT (TAYLOR & FRANCIS LTD, 2016)
The aim of this study is to determine the cutaneous wound healing effects of the ethanol extract of Cotinus coggygria leaves in rats by excision wound model to provide scientific evidence for the traditional use of C. coggygria Scop. The levels of malondialdehyde, catalase, superoxide dismutase, glutathione and hydroxyproline were investigated in wound tissues. Histopathological examination was also performed. The hydroxyproline content of the granulation tissue and the glutathione levels were both significantly higher in the treatment group than in the control group (p < 0.05 for both); while the malondialdehyde levels were significantly lower in the treatment group (p < 0.05). These results were supported with histological results. The ethanol extract of C. coggygria Scop could be considered as an effective agent in wound healing in accordance with its traditional use.
Keywords: wound healing; hydroxyproline; Cotinus coggygria Scop; CONSTITUENTS; CHELATION; COLLAGEN